Web marketplace development for used car sales based on progressive web apps - Imam Soleh Marifati; Ubaidillah Ubaidillah (Sean Institute, 2024)
The prospect of buying and selling used cars shows a significant increase. This is because public interest in used cars is quite high. Used cars are an alternative for certain groups of people to meet their needs for affordable vehicles with good quality. Digital transformation is a breakthrough that can be chosen by used car buying and selling businesses. With digital technology, especially the use of the internet, it is possible to access information and transactions without limits of space and time. This condition is often found on social media platforms used by traders to offer used vehicles for sale online. The use of social media has weaknesses because often information about vehicles being traded is mixed with other irrelevant information, making it difficult for consumers to make choices and can reduce trust in the products being sold. In this research, a market place application was developed for buying and selling used cars, especially for traders in the Purwokerto city area. The developed application uses progressive web apps (PWA) technology where web-based applications can be installed on mobile devices like native applications.